Spatial and Temporal Variation Characteristics of Drought in Guizhou Province Based on VCI and Division of Arid Regions - DAI Renli; ZHONG Jiusheng (Renmin Zhujiang)
Due to its unique dual hydrological structure of surface water and groundwater and typical karst low mountain and hilly landform area,the agricultural ecological environment of Guizhou Province is extremely fragile,and it is prone to agricultural disasters caused by meteorological factors,leading to reduced agricultural production.This paper calculates the VCI of Guizhou Province from 2001 to 2018 by remote sensing technology,explores the agricultural drought situation in Guizhou Province,divides the spatial distribution of seasonal arid regions in Guizhou Province with ArcGIS spatial overlay analysis,and analyzes the VCI trend characteristics of Guizhou Province through the unary linear trend method.The results show that:①The seasonal and inter-annual VCI in Guizhou Province generally show a downward trend,most obviously in karst areas,followed by non-karst areas;②Guizhou Province's seasonal droughts are mainly spring and winter droughts,and dry karst areas is a drought-prone area;③The drought time characteristics of Guizhou Province are mainly seasonal continuous drought and three-season continuous drought.